Alignment of site versus adjudication committee–based diagnosis with patient outcomes: Insights from the Providing Rapid Out of Hospital Acute Cardiovascular Treatment 3 trial. (April 2016) - Sepehrvand, Nariman; Zheng, Yinggan; Armstrong, Paul W; Welsh, Robert; Goodman, Shaun G; Tymchak, Wayne; Khadour, Fadi; Chan, Michael; Weiss, Dale; Ezekowitz, Justin A
Background: Adjudication by an adjudication committee in clinical trials plays an important role in the assessment of outcomes. Controversy exists regarding the utility of adjudication committee versus site-based assessments and their relationship to subsequent clinical events. Methods: This study is a secondary analysis of the Providing Rapid Out of Hospital Acute Cardiovascular Treatment-3 trial, which randomized patients with chest pain or shortness of breath for biomarker testing in the ambulance. The emergency department physician diagnosis at the time of emergency department disposition was compared with an adjudicated diagnosis assigned by an adjudication committee. The level of agreement between emergency department and adjudication committee diagnosis was evaluated using kappa coefficient and compared to clinical outcomes (30-day re-hospitalization, 30-day and 1-year mortality). Results: Of the 477 patients, 49.3% were male with a median age of 70 years; hospital admission rate was 31.2%. The emergency department physicians and the adjudication committee disagreed in 55 cases (11.5%) with a kappa of 0.71 (95% confidence interval: 0.64, 0.78). The 30-day re-hospitalization, 30-day mortality, and 1-year mortality were 22%, 1.9%, and 9.4%, respectively. Although there were similar rates of re-hospitalization irrespective of adjudication, in cases of disagreement compared to agreement between adjudication committee and emergency department diagnosis, there was a higher 30-day (7.3% vs 1.2%, p = 0.002) and 1-year mortality (27.3% vs 7.1%, p < 0.001). Conclusion: Despite substantial agreement between the diagnosis of emergency department physicians and adjudication committee, in the subgroup of patients where there was disagreement, there was significantly worse short-term and long-term mortality.